Hydrological and Biogeochemical Patterns in the Sicily Channel: New Insights From the Last Decade (2010-2020) - Placenti, Francesco; Torri, Marco; Pessini, Federica; Patti, Bernardo; Tancredi, Vincenzo; Cuttitta, Angela; Giaramita, Luigi; Tranchida, Giorgio; Sorgente, Roberto (Frontiers in Marine Science, 2022)
The hydrological and biogeochemical time series from 2010 to 2020 have highlighted specific relationships and trends in oceanographic processes and nutrient patterns in the Sicily Channel. Specifically, temperature and salinity time series in the intermediate waters showed a sharp annual increase of about 0.06°C and 0.09 within the period 2010-2020, at rates that are about 50% higher than what observed within the previous decade. Similar trends were also present in deep waters, although with lower variations of both temperature and salinity. The time series in the intermediate water, also highlighted the presence of quasi cyclic fluctuations that can be associated with the alternation of the circulation modes (cyclonic and anticyclonic) of the Northern Ionian Gyre. Moreover, an opposite trend emerged by comparing the nutrients and salinity time series in intermediate waters, while similar patterns has been evidenced between nutrients and chlorophyll-a concentration. This latter finding is not consistently present in the Mediterranean area, suggesting the need of further studies on a wider scale.